Assessment of effects of IR and IPC on activities of cytochrome P450 isozymes in rats by a five-drug cocktail approach. (February 2014) - Li, Qin; Liu, Ying; Jiao, Jianjie; Zhang, Caili; Lou, Jianshi
Abstract Background and objective: To evaluate the effects of ischemia and reperfusion (IR) and ischemic preconditioning (IPC) on the metabolic activities of cytochrome P450 (CYP) isozymes in rats by a five-drug cocktail approach. Methods: Cocktail approach was used to evaluate the influence of IR and IPC on the activities of CYP1A2, CYP2C9, CYP2E1, CYP2D6 and CYP3A4, which were reflected by the changes of pharmacokinetic parameters of five specific probe drugs: caffeine, chlorzoxazone, tolbutamide, metoprolol and midazolam, respectively. Rats were randomly divided into IR, IPC and sham groups, and then injected the mixture of five probe drugs. Blood samples were collected at a series of time-points and the concentrations of probe drugs in plasma were determined by a HPLC method with UV detection. The pharmacokinetic parameters were calculated by the software of DAS 2.0. Results: The parameters including t1/2β, CLs, AUC, MRT and K10 exhibited a similar tendency for both IR and IPC groups. Compared with sham group, CLs and K10 of five probe drugs were significantly lower (p < 0.05), AUC and t1/2β of five or some probe drugs were significantly increased in IR and IPC groups (p < 0.05). Compared with IPC group, CLs of five probe drugs were decreased and AUC were significantly increased in the IR group (p < 0.05). Conclusion: IR can variably decrease the activities of CYP isozymes in rats and this decrease can be attenuated by IPC.